Three new species of free-living nematodes from Vietnamese water bodies - Gagarin, V. G.; Nguyen Vu Thanh (Zoologičeskij žurnal, 2003)
Three new species of nematodes found in water bodies of Vietnam are described and illustrated. Terschellingia elegans sp. n. is close to T. supplementa Tchesunov 1978, but differs in the less slender body, shorter cephalic setae, presence of well-developed stoma and absence of somatic and cervical setae. Adoncholaimus parvus sp. n. differs from A. lepidus (de Man, 1889) and A. aralensis Filipjev, 1924 in the narrower stoma, shorter tail, longer spicules and absence of numerous precloacal setae in males. Dorylaimus parvus sp. n. differs from D. afghanicus Andrássy, 1960 in the smaller body, shorter tail in females, shorter spicules, less number of supplements in males and vulva situated nearly to body middle, and differs from D. carinatus Thorne & Swanger, 1936 in the shorter tail in females, shorter spicules, a less number of supplements in males and vulva situated further from body middle.
NeMys doc_id: 17931